HAK-HAK TAHANAN DALAM MASA COVID-19 DI RUMAH TAHANAN NEGARA KELAS II B KOTABUMI - Muhammad Idran; Muhammad Hadidi (Universitas Muhammadiyah Kotabumi, 2022)
Indonesia is a country based on law (rechtsstaat). This has a legal consequence that in the Indonesian state, the implementation of state power in a broad sense must and must always be based on law, because that law gives legitimacy as well as provides boundaries that are the authority of the state (government). A suspect who is detained and whose rights are violated can use legal instruments in accordance with the applicable laws and regulations in order to obtain legal certainty and a sense of justice for himself, especially in the protection and implementation of the rights of a detained suspect. The spread of the Covid-19 virus (Corona Virus Disease 2019) which occurred from the beginning of 2020 until now has had a major impact on the Correctional Persons, hereinafter referred to as WBP, in the Class II B State Detention Center in Kotabumi. So the question arises, How are the rights of prisoners in the Class II B State Detention Center in Kotabumi implemented? What efforts can be made by detainees if the implementation of prisoners' rights at the Class II B Kotabumi State Detention Center is not in accordance with the laws and regulations? The approach method used by the author in this study is a mixed approach, namely normative and empirical. The normative approach is the approach that the author obtained through books and laws and regulations, both those regulated in the Act, the Criminal Code, the Criminal Procedure Code and other regulations related to the writing of this thesis. The empirical approach is the approach that the author obtained through the interview process and collecting information through the State Detention Center Class II B Kotabumi. Based on the results of this study, the authors conclude that the rights of WBP prisoners and temporary detainees have been well fulfilled, such as in the case of the program to reduce prison terms during the Covid-19 pandemic, which has been fulfilled in accordance with applicable laws and regulations. However, it would be better if the correctional officers paid more attention to the rights of prisoners related to the prevention of the Covid-19 virus in accordance with government recommendations and applicable government regulations. Considering that there are quite a number of WBP in the Class II B State Detention Center in Kotabumi, so there is a need for additional guidance by supervisory officers for prisoners properly and effectively. The lack of guidance in the detention center occurs because of obstacles, one of which is seen from external factors, namely in the form of a lack of coaching funds, coaching staff, and facilities and infrastructure. So, it would be nice if the existing obstacles can be met so that the coaching can run well.